Potensi Eceng Gondok (Eichhornia Crassiper) Sebagai Kalorimetri Kation dan Anion - Nurmala Sari (Jurnal Multidisiplin Madani, 2022)
One of the compounds contained in water hyacinth is delhinidine 3-diglucosin. The compound is a compound that has the potential as a sensor for cations and anions because it has active groups, namely OH- and O. This study used the maceration method, then several tests were carried out, which obtained a water content of 10.24% and an ash content of 14.67%. The solvatochromic test on distilled water, methanol and acetone showed that there was a bathochromic shift and a hipsochromic shift. Meanwhile, the ionochromic qualitative test showed that the identification of cations was better than the anion test. The cation results showed that in distilled water (Yellow), water hyacinth could identify Cu2+ and Fe3+ (Green), in methanol solvent (Green) for Fe3+ metal (Yellow) while in acetone solvent (Green) it could identify Pb2+, and Fe3+ ( Yellow).